Clinical evaluation and disease management of PI-RADS 3 lesions. Analysis from a single tertiary high-volume center. (2nd September 2020) - Di Trapani, Ettore; Musi, Gennaro; Ferro, Matteo; Cordima, Giovanni; Mistretta, Francesco Alessandro; Luzzago, Stefano; Bianchi, Roberto; Cozzi, Gabriele; Alessi, Sarah; Catellani, Michele; Matei, Deliu Victor; Jereczek-Fossa, Barbara Alicja; et al.
Abstract: Objective: To evaluate the clinical and pathological implications of Prostate Cancer (PCa) patients with a Prostate Imaging - Reporting and Data System (PI-RADS) 3 lesion at multi parametric magnetic resonance imaging (mpMRI). Methods: We included 356 patients with a PI-RADS score 3 lesion at mpMRI who underwent prostate biopsy for a suspect of PCa at a single tertiary high-volume centre between 2013 and 2016. We developed Uni- (UVA) and multi variable (MVA) logistic regression analyses assessing the predictors of three endpoints: 1) diagnosis of PCa, 2) active surveillance (AS) criteria and 3) clinically significant (CS) PCa at final pathology. Results: PCa was diagnosed in 285 patients (80%), out of these 154 (56%) were eligible for AS according to Prostate Cancer Research International Active Surveillance (PRIAS) criteria. Over the 228 (64%) patients who underwent surgery, 93 (40.8%) had a CS disease at final pathology. Hundred and ninety-three (84.6%) had a pT2 disease and 35 (15.4%) had a pT3 disease. The size of the main lesion, age, PSA and prostate volume efficiently predicted PCa at MVA (all p < 0.05). None of our predictors were significantly associated with AS characteristics. Over those patients who underwent surgery, the biopsy Gleason Score ( p = 0.007) efficiently predicted a CS PCa at final pathology. Conclusions: mpMRI-detected PI-RADS 3 lesions should be sent to a prostate biopsy if other clinical parameters suggest the presence of a PCa. In case of diagnosis of a PCa, patients should undergo confirmatory biopsy before being included in AS protocols to avoid underestimation of a CS disease.